Contextualising thesis process digitalisation at a university in Ghana - Oliveira Leite, Lais; Lagstedt, Altti; Awuni Kolog, Emmaunel; Tsupari, Kaisa (Australasian Journal of Educational Technology, 2023)
This study utilised thesis process as a case to investigate how its digitalisation can improve operational and pedagogical processes. A thesis management system (Wihi), developed during thesis process digitalisation in a Finnish university, was piloted at the University of Ghana. The purpose was to see if the system supported the thesis process at the University of Ghana and if good practices were transferable. A total of 44 system users from the University of Ghana participated in the pilot to develop a more fluent and effortless thesis process for students, supervisors and coordinators. Eight of them were selected as informants for the study through interviews and a focus group. The data were coded and analysed using theory-based content analysis. The study’s findings reveal that the manual thesis process in use was laborious and dispersive, resulting in supervisors and coordinators frequently losing track of students’ work progress. The digitalisation improved the administrative and educational experiences of all the parties concerned, helping students and supervisors to maintain a transparent thesis process-based discussion and to better plan writing schedules. Additionally, coordinators were able to use data from thesis processes to support their decision-making. The results demonstrate that the good practices of thesis process digitalisation can be transferred across these two universities. Implications for practice or policy Universities should prioritise user-friendly digital tools that improve thesis work processes and provide valuable data for educational and administrative decision-making. When assessing technology acceptance in cross-cultural work settings, decision-makers can focus more on common core processes than cultural factors thanks to the increasing effects of globalisation and digitalisation. University leaders should offer appropriate training for education staff to promote smoother technology adoption, which can effectively reduce resistance to change.